IMPLEMENTASI PELAYANAN TERPADU SATU PINTU (PTSP) DALAM MEWUJUDKAN ASAS CEPAT, SEDERHANA, BIAYA RINGAN DI PENGADILAN AGAMA ARGA MAKMUR - Stevri Iskandar; Dimas Ghozi Al Fajri; Ramdhan Ryovi Nesta (Jurnal Riset Multidisiplin Edukasi, 2025)
The purpose of this study is to examine and analyze the implementation of the One-Stop Integrated Service (PTSP) in realizing the principles of fast, simple, and low-cost justice at the Religious Court of Arga Makmur. This research focuses on how PTSP operates as a front-line service in handling administrative processes and public requests related to court cases. The study uses a juridical empirical method with a descriptive analytical approach. Primary data were obtained through interviews and observations during internship activities at the Religious Court of Arga Makmur, while secondary data were collected from legislation, court regulations, and relevant literature. The results show that the implementation of PTSP has improved service quality by simplifying procedures, shortening processing times, and increasing transparency and accountability. However, several obstacles remain, such as limited human resources, inadequate digital infrastructure, and low public legal awareness. These findings indicate that continuous improvement in human resource capacity and technology utilization is essential to fully realize the principles of fast, simple, and low-cost justice.